ENHANCING STUDENT ENGAGEMENT THROUGH THE USE OF INTERACTIVE METHODS IN SCHOOL EDUCATION - Qodirova , Dilnura; Saitov , Sirojiddin (Scientific practical conference, 2026)
This article explores the importance of using interactive teaching methods in school education to increase students’ engagement and learning activity. In modern educational environments, traditional teacher-centered approaches are gradually being replaced by student-centered methodologies that emphasize participation, collaboration, and critical thinking. The study analyzes various interactive methods such as group work, discussions, brainstorming, role-playing, and problem-based learning. It also examines their impact on students’ motivation, communication skills, and academic performance. Furthermore, the paper highlights the advantages and challenges of implementing interactive methods in classroom practice and provides recommendations for effective application. The findings suggest that interactive teaching strategies significantly contribute to the development of active, independent, and creative learners.